Manual de procedimientos para el cumplimiento de las obligaciones tributarias de los Micromercados de la cabecera cantonal de Pindal, provincia de Loja, período 2023. - Herrera Infante, María Belén (2024)
The Curricular Integration Work entitled "PROCEDURAL MANUAL FOR COMPLIANCE WITH TAX OBLIGATIONS OF THE MICROMARKETS IN THE HEAD CANTON OF PINDAL, LOJA PROVINCE, 2023 PERIOD" was developed with the aim of formulating procedures in the tax area to uphold a logical and sequential order facilitating the development of functions and activities for proper recording and control of operations conducted within the micromarkets. The manual constitutes an essential tool, as well as a support and guidance instrument that allows owners to have broader and more detailed knowledge in the execution of their activities and tax procedures. It facilitates a proper control of operations, and ensures efficient compliance with tax obligations, leading to timely decision-making that maximizes business resources. Thus, it fosters a tax culture to achieve better compliance levels. The primary statistical universe in the head canton of Pindal comprises 56 micromarkets. Owners were surveyed to gather important data concerning their familiarity with and access to a procedural manual for tax obligations. The research findings revealed a lack of awareness among taxpayers in Pindal’s micromarkets regarding their tax obligations and associated benefits, potentially resulting in penalties and fines. Subsequently, policies and procedures focused on the tax process were developed, detailing compliance with tax obligations, so that micromarkets owners are aware of the taxes they are required to declare, as well as the annexes they must submit according to the dates established in accordance with current regulations. Finalmente, se diseñó flujogramas para el proceso de cumplimiento de las obligaciones tributarias con el objetivo de visualizar y comprender de una manera sencilla los procesos a seguir para la presentación de declaraciones y anexos. En la parte complementaria del presente trabajo de titulación se hacen constar las conclusiones con las respectivas recomendaciones las mismas que generan un aporte importante del presente trabajo. Finally, flowcharts were designed for the tax obligation compliance process with the aim of visualizing and understanding in a simple way the processes to follow for the presentation of declarations and annexes. In the complementary part of this research work, conclusions and recommendations are included, which make an important contribution from this work.